Knowledge and attitudes of Czaplinek Municipality residents with regard to colorectal cancer prevention - Jaroszyńska, Zuzanna; Andrusiewicz, Mirosław; Wiśniewska, Katarzyna (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Colorectal cancer (C18-C21) is currently the second cause of cancer-related deaths among men and the third among women in Poland. The aim of the paper was to assess the knowledge and attitudes of the Czaplinek Municipality residents with regard to colorectal cancer prevention. Material and Method: The research was conducted between October and December 2020 among 238 inhabitants of the Czaplinek Municipality, located in Zachodniopomorskie Voivodeship, Drawsko District. The research tool was an original survey questionnaire, consisting of 22 closed-ended questions. The results obtained were processed in a Microsoft® Excel® 2016 MSO spreadsheet and statistically analysed using Statistica® software (TIBCO Software Inc.). Results: The majority of the respondents (74.8%) knew that early diagnosis of colorectal cancer significantly increases the chances of recovery. Only half of the respondents (50.8%) were aware that this cancer can develop asymptomatically. Knowledge of risk factors and symptoms of colorectal cancer in the study group was low. The respondents’ overall level of knowledge about colorectal cancer and its prevention was most often sufficient (62.5%). Less than a third of the respondents (31.5%) had heard of the Colorectal Cancer Screening Programme. Conclusions: The level of knowledge and attitudes of the Czaplinek Municipality inhabitants regarding colorectal cancer and its prevention is definitely unsatisfactory. There is an urgent need for intensive educational activities, focusing primarily on promoting colorectal cancer screening.